THE ANALYSIS OF STUDENTS’ PRONUNCIATION ERRORS IN READING ALOUD - Mutiana Budiman; Ikeu Kania (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2019)
It was aimed to identify students’ pronunciation errors in reading aloud by finding out how far the students’ pronunciation errors in reading aloud and kind of words which are pronounced by the students through reading aloud. Qualitative method was used to find out the fact and the evidence of students’ pronunciation errors in reading aloud. The observation and the interview were conducted to explore the student’s experience and their problems in pronouncing English.The findings revealed that there were satisfactory results proved that the students made pronunciation errors in six part of speech; Nouns, Verbs, Adjectives, Adverbs, Prepositions and Conjunction. It was found that 26 pronunciation errors in noun (26.8%), 49 pronunciation errors in verb (50.5%), 6 pronunciation errors in adjective (6.2%), 12 pronunciation errors in adverb (12.4%), 3 pronunciation errors in preposition (3.1%) and 1 pronunciation error in conjunction (1.03%) from 7 students who had read the same narrative text. The reasons why the students made errors in pronouncing the words were the students have difficulties in pronouncing and spelling the words with affixes and prefixes in consonants, vowels, and diphtongs. They are: upon, aunt, lived, died,answered, knocked, cottage, dwarf, enough.